Inisiasi Pengelolaan Metode Pemberian Asuhan Keperawatan Primer di RS X - Tulende, Alfani; Handiyani, Hanny; Wildani, Andi Amalia; Harpendewisasmita, Harpendewisasmita (Journal of Telenursing (JOTING), 2024)
This study aims to analyze and design the implementation of change through the initiation of management of primary nursing care delivery methods. The method used is a case report with interviews, observations, document reviews, and questionnaire surveys as well as problem analysis using fishbone diagrams. The results of the analysis showed that the method of providing nursing care in the inpatient room was not optimal, so through a change approach using the Kurt Lewin;s Change Model, the initiation of management of primary nursing care delivery methods was carried out. In conclusion, optimizing nursing care delivery methods through the implementation of primary nursing care management methods with a systematic and structured management approach has the potential to improve the quality of nursing services. Keywords: Initiation Of Management, Kurt Lewin's Change Model, Primary Nursing Method